Model TPACK dalam Kolaborasi Canva Creator dan Guru dalam Pengembangan Media Pembelajaran - Muhammad Nur Setiawan; Mohamad Joko Susilo (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
In the digital era, teachers are required to present innovative learning media, yet they are often constrained by time limitations and technical design skills. This study aims to analyze the implementation of the TPACK model in the collaboration between teachers and Canva Creators at Studio Kreasi Cantik, Magelang, as a solution for developing effective learning media. This research employs a qualitative case study approach. Data were collected through observations of the collaboration process and the utilization of secondary data from the designer performance monitoring information system to measure the effectiveness of media production. The results indicate that the collaboration operates systematically through the integration of three TPACK components: (1) Technological Knowledge is reflected in the creators' mastery of the Canva platform, supported by a quality monitoring system; (2) Pedagogical Knowledge is implemented through the adaptation of designs to teachers' instructional strategies; and (3) Content Knowledge is maintained through a validation process of religious material accuracy by the teachers. The high utility of the studio’s digital assets (over 15,000 followers) proves that this collaboration model provides significant value to educators. Finally, The synergy between technology practitioners and teachers is capable of creating a modern learning ecosystem without compromising the quality of the material substance.